Binilik the concealed women of the dulangan manobo in Kulaman Valley, Sultan Kudarat - Delos Reyes, Harley Farrah C.
This study entitled ?Binilik: The Concealed Women of Dulangan Manobo in Kulaman Valley, Sultan Kudarat? described the Dulangan Manobos' practice of keeping an unmarried daughter of a datu from public view. The study describes the training of the binilik from the girl's adolescence up to her married life. It also includes the marriage rites involving the binilik. A binilik is pared from any task that requires her to be outside the house. Marriage of the binilik is arranged by her parents and the parents of her prospective partner. Marriage of a binilik entails the discussion of the sunggod or bride price. Most of the data were through verbal acocunts from the last two women who experienced being a binilik. Perceptions from other Dulangan Manobo about the practice were also taken into account.keeping a binilik gives the family a higher social status because they were able to exempt the young woman from contributing in their daily subsistence. The binilik demanded a very high value but was not seen as a mere commodity. The girl was considered precious to the parents and the exchange of the bride price did not imply the selling of the woman. Rather, the higher the bride price was made as payment for raising the child with knowledge on the domestic responsibility. The researcher also examined how the influence of social factors such as the onset of education, religion, influx of lowlanders and the change in the economic condition of the Dulangan Manobo affected the practice of keeping a binilik. It can be said that these factor's influence to the Dulangan Manobo community have later led to the disappearance of the practice.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao